1990
DOI: 10.1007/bf01740778
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry of the galliform cecum: A comparison between Gambel's quail and the domestic fowl

Abstract: Tissues from the proximal, middle, and distal regions of the ceca of Gambel's quail and domestic fowl were examined by scanning and transmission electron microscopy. Cellular and subcellular structures, including epithelial cell height, mitochondrial volume fraction, microvillous surface area, proportion of goblet cells, and junctional complex characteristics, were quantified by a variety of stereologic procedures and other measurement techniques. The mucosal surface of quail cecum shows a much more highly dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
3
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
5
3
0
Order By: Relevance
“…The values of MAF obtained in the present study fell between 11 (medial cecum) and 38 (jejunum), and were consistent with the values calculated by Strong et al (1990) in the cecum of Leghorn chickens, which fell between 8 and 17. They also agreed with the stereological data of Elbrond et al (1991) obtained in the coprodeum of 3-to 4-wk-old chickens fed a high-NaCl diet (32 jan 2 per cell).…”
Section: Apical Surface Areasupporting
confidence: 91%
See 1 more Smart Citation
“…The values of MAF obtained in the present study fell between 11 (medial cecum) and 38 (jejunum), and were consistent with the values calculated by Strong et al (1990) in the cecum of Leghorn chickens, which fell between 8 and 17. They also agreed with the stereological data of Elbrond et al (1991) obtained in the coprodeum of 3-to 4-wk-old chickens fed a high-NaCl diet (32 jan 2 per cell).…”
Section: Apical Surface Areasupporting
confidence: 91%
“…From the point of view of regional comparison, our results fully agreed with the proximo-distal decrease in MAF described by Strong et al (1990) for the chicken cecum. Also, the similar degree of development of microvilli in duodenum and jejunum was consistent with that observed in the rat (Stenling and Helander, 1981) and the mouse (Ferraris et al, 1989) but differed from the pattern described for the iguana and the wood rat (Ferraris et al, 1989).…”
Section: Apical Surface Areasupporting
confidence: 90%
“…It has been suggested that goblet cells are responsible for secretion of mucus that lubricate the caecal contents are more abundant in the proximal part of the cecum (Kumary et al, 2009;Strong et al, 1990) Although physiologic significance of different mucin subtypes has not been fully understood yet, it is suggested that since particularly sulfated mucins is less degredable by bacterial glycosidases, acidic mucins protect the mucosa against bacterial translocation (Deplancke & Gaskins, 2001;Fontaine et al, 1996). It has been suggested that goblet cells express especially acidic mucins in intestinal regions contains densely populated by microbes.…”
Section: Discussionmentioning
confidence: 99%
“…The epithelium lining the villi, mucosal folds and crypts of cecum have been reported to consist of a single layer of tall columnar cells interspersed with goblet cells (Kumary et al, 2009; Paul et al, 2017). It has been suggested that goblet cells are responsible for secretion of mucus that lubricate the caecal contents are more abundant in the proximal part of the cecum (Kumary et al, 2009; Strong et al, 1990). Literature of ontogeny of goblet cell formation and distribution in the cecum of chickens are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, the authors agreed that distal part of the ceca does not have villi as the short villi existing in the middle part of ceca gradually get faded out. Because of fermentation and other bacterial or chemical processes that have been shown to occur in the ceca, it is logical to conclude that cecal epithelium could be a site for primary absorption of nutrients or for re-absorption of electrolytes or amino acids derived from the urine (Strong et al, 1990). Thomas (1982) in his comprehensive review of water and electrolyte absorption in fowl stated that water absorption in the gut does not occur until the end of ileum, and it is mainly due to reabsorption of electrolytes and water of intestinal and renal origin in the ceca.…”
Section: Discussionmentioning
confidence: 99%